Identifying key factors for successful formulation and implementation of healthcare policies on non-communicable diseases: a multinational analysis - Babaita, Abdulfatai Olamilekan; Jahan, Yasmin; Nakamura, Ryota; Moriyama, Michiko (Frontiers in Public Health, 2024)
Objectives Non-communicable diseases (NCDs) are a major public health concern that accounts for 74% of global deaths each year. The increasing burden of NCDs exhausts public health resources and threatens the achievement of the 2030 agenda for sustainable development. The purpose of this study is to thematically analyze the contributory factors in the health policy process and reforms to strengthen the prevention of NCDs across borders, as well as the milestones achieved through the process of policy-making, change, and implementation. Method This study informs and draws on the findings of contributory factors in the health policy process for preventing NCDs across borders: United States, England, Sweden, Bangladesh, Singapore, South Korea, and Thailand. Ten experts from the seven countries were recruited purposively for a semi-structured interview (e-Interview) on the NCD policy-making process in their countries, either through health ministries or the authors’ network. This descriptive qualitative study design is guided by the “Three I’s” framework of public policy (institutions, ideas, and interests). In addition to the information obtained from the interviewee, data were also sourced from relevant documents and homepages suggested by the interviewee, as well as health homepages of the countries. Result The following themes were generated: (1) environmental policies and social determinants, (2) multistakeholder involvement, (3) interministerial collaboration, (4) independent evidence and review institution, (5) integrated health data, and (6) primary care system. There was a shift from individual-targeted policies to environmental policies and social determinants. Notably, national campaigns were developed through non-governmental organizations (NGOs) for the primary prevention of NCDs. Conclusion The shift from behavioral modification and treatment to social determinants is important. NCDs are broad and require a multisector and multilevel approach. Establishing an organization or hierarchical body to overlook NCDs could result in increased awareness, focus, and surveillance and enhance the policy process.